2023
DOI: 10.1101/2023.03.06.531261
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The EDC4-XRN1 axis controls P-body dynamics to link mRNA decapping with decay

Abstract: Deadenylation-dependent mRNA decapping and decay is the major cytoplasmic mRNA turnover pathway in eukaryotes. Many mRNA decapping and decay factors associate with each other via protein-protein interaction motifs. For example, the decapping enzyme DCP2 and the 5’-3’ exoribonuclease XRN1 interact with enhancer of mRNA decapping protein 4 (EDC4), a large scaffold that has been reported to stimulate mRNA decapping. mRNA decapping and decay factors are also found in processing bodies (P-bodies), evolutionarily co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…6d, e). To test whether the observed enrichment of shortened genes is specific to the SGs, we also tested for association with processing bodies (P-bodies), membraneless organelles enriched in de-capping factors and exoribonucleases, essential for RNA decay under normal, non-stress conditions (Brothers et al, 2023). We re-analyzed previously published data from HEK293 cells (Matheny et al, 2019), but in contrast to SGs, we found no association between P-body localization and gene lengths (Sup.…”
Section: Restoring Ribosome Density Inhibits Stress-induced Rna Decaymentioning
confidence: 97%
“…6d, e). To test whether the observed enrichment of shortened genes is specific to the SGs, we also tested for association with processing bodies (P-bodies), membraneless organelles enriched in de-capping factors and exoribonucleases, essential for RNA decay under normal, non-stress conditions (Brothers et al, 2023). We re-analyzed previously published data from HEK293 cells (Matheny et al, 2019), but in contrast to SGs, we found no association between P-body localization and gene lengths (Sup.…”
Section: Restoring Ribosome Density Inhibits Stress-induced Rna Decaymentioning
confidence: 97%
“…Conversely, inhibition of deadenylation results in smaller P-bodies (59). Interestingly, disrupting the EDC4-XRN1 interaction inhibits mRNA decapping, stabilizes miRNA-targeted mRNAs, and increases Pbody size in HeLa cells (60). The increase in P-body size in nhl-2(RBlf) but not in the RING mutant, correlates with the severity of the alae defects observed.…”
Section: Nhl-2 Crystal Structure Reveal Similarities and Differences ...mentioning
confidence: 99%
“…On its own, this hypomorphic allele exhibited ~70% embryonic lethality at 16°C (Figure 4C). dcap-2(0) was synthetic lethal with mir-35-41(nDf50), as we could not obtain a single viable homozygous dcap-2(0); mir- [35][36][37][38][39][40][41] animal. Individual edc-3(0) or edc-4(0) mutants exacerbated mir-35-41(nDf50) embryonic lethality to 91% and 93%, while their combined deletion exacerbated lethality to ~99% (Figure 4C).…”
Section: Edc-3 Inhibits Somatic Accumulation Of Ifet-1 Car-1 and Cgh-1mentioning
confidence: 99%
“…In C. elegans embryos, P-bodies are found in the somatic and germline blastomeres and are distinct from P/germ granules, which specifically form in the germline lineage 36,37 . Originally proposed to be active sites for mRNA decay 38 , several lines of evidence support the idea that P-bodies instead store and protect silent mRNAs from decapping and decay 33,[39][40][41] . However, as P-bodies seem to form as a consequence of translational repression, some papers even challenged whether they represent active regulatory sites per se 21,42 .…”
Section: Introductionmentioning
confidence: 96%